Adjusting prices in the many-to-many assignment game - Marilda Sotomayor (Brown University, Department of Economics, 2008)
Starting with an initial price vector, prices are adjusted in order to eliminate the demand excess and at the same time to keep the transfers to the sellers as low as possible. In each step of the auction, to which sellers should those transfers be made (minimal overdemanded sets) is the key definition in the description of the algorithm. Such approach was previously used by several authors. We introduce a novel distinction by considering multiple sellers owing multiple identical objects and multiple buyers with a quota greater than one consuming at most one unit of each seller's good. This distinction induces a necessarily more complicated construction of the overdemanded sets than the constructions existing in the literature, even in the simplest case of additive utilities considered here. As the previous papers, our mechanism yields the minimum competitive equilibrium price vector. A procedure to find the maximum competitive equilibrium price vector is also provided.
Keywords: C78; D78; 330; matching; stable payoff; competitive equilibrium payoff; optimal stable payoff; lattice; Matching; Spieltheorie; Auktionstheorie; Theorie